Prevalence and treatment tactics of nonspeciﬁc urinary tract infection in tuberculosis patients - Z. R. Rashidov; S. I. Azimov (Туберкулез и болезни лёгких, 2022)
The objective: to study prevalence and evaluate the eﬃcacy of therapy and prevention of nonspeciﬁc urinary tract infection (NUTI) in tuberculosis patients as well as the possibility of combining them with anti-tuberculosis therapy.Subjects and Methods. 936 patients with various localizations of tuberculosis at the age from 18 to 96 years old were examined. Men made 447 (47.8%), and women – 489 (52.2%). NUTI was diagnosed based on the following criteria: the presence of typical symptoms, leukocyturia and bacteriuria detected by urine microscopy, positive results of urine culture for nonspeciﬁc bacterial population, and negative urine tests for tuberculous mycobacteria.Results. The prevalence of NUTI among tuberculosis patients made 174 (18.6%) out of 936 patients, it was found among all forms of TB but most frequently in urogenital tuberculosis (74.1%). Prophylactic treatment tactic (antibacterial therapy and the herbal formulation of Kanefron N) was oﬀered. Treatment eﬃcacy made 94.6%, while patients received anti-tuberculosis therapy, and the combination of drugs caused no adverse reaction in any patient. When choosing a therapeutic tactic, it is necessary to take into account the presence of structural and functional changes in the urinary tract which reduce treatment eﬃcacy.